The effect of unemployment on the level of wages in the enterprise sector in Poland (2000-2014) - Maciej Szczepanik (The Central European Review of Economics and Management (CEREM), 2019)
Aim: In the first section of the paper, a brief outline is presented of the economic theory delineating the concept of unemployment and its association with the level of wages. The concept of unemployment and contemporary theories of this phenomenon are discussed. The paper also includes criticism of certain parts of neoclassical theory of the labour market which represents the author's own thoughts. It is concerned especially with the equilibrium price on this market, in other words, the level of wages and labour supply curve. The aim of the paper is to analyze the effect of unemployment on the level of wages in the enterprise sector in Poland.Design / Research methods: Linear correlation between monthly data from 2000 to 2014 were used. Certain measures were employed, such as differencing or shifting time series (in both directions), to avoid the effect of seasonality, that is, of apparent correlation on the study results, and to determine precisely the direction of correlation between variables. This methodology allows for increased reliability of the results produced.Conclusions / findings: Thanks to that, it was possible to observe a clear statistically significant negative effect of unemployment on the level of wages in Poland in the analyzed period. This effect, on both nominal and real wages, was lagged by one month.Originality / value of the article: The results of the research represent scientific value added of the paper and can be taken into consideration while making decisions concerned with the country's macroeconomic policy.
Keywords: C10; 330; unemployment; level of remuneration; wages; linear correlation